Growth and Yield Performance of Fluted Pumpkin (Telferia Occidentalis Hook F.) to Wood Shaving Biochar and Poultry Manure in Ikorodu, Lagos, Nigeria - Godonu Kolawole Gbemavo; Sanni Kehinde Oseni; Alo Rock Anayo Peter; Eleduma Ajayi Festus (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
In many tropical cropping systems, low soil fertility is a significant factor that hinders the development of vegetable crops. In order to get a good yield, it is necessary to increase the soil's nutrient status to satisfy the crop's needs, hence maintaining the soil's fertility status. To determine the effects of Wood Shavings Biochar (WSB) and Poultry Manure (PM) on the performance of fluted pumpkin (Telferia occidentalis), this study was conducted at the Teaching and Research Farms, Department of Crop Production and Horticulture, Lagos State Polytechnic, Ikorodu, Lagos State, Nigeria. Five (5) treatments-7.5 t/ha WSB, 7.5 t/ha PM, 2.5 t/ha WSB + 5 t/ha PM, 5 t/ha WSB + 2.5 t/ha PM, and control-were administered to the plots two weeks prior to planting. The experiment was set up using a Randomized Complete Block Design (RCBD). Vine length, leaf count, vine girth, and leaf yield per plot were among the data obtained. They were statistically examined using Analysis of Variance (ANOVA), and the Duncan Multiple Range Test (DMRT) was used to compare the means of the treatments at a 5% level of probability. The results revealed that the optimum performance was provided by 2.5 t/ha WSB + 5 t/ha PM and 7. 5 t/ha PM, followed by 5 t/ha WSB + 2.5 t/ha PM and 7.5 t/ha WSB in terms of enhancing the soil nutrients, which in turn improved growth and yield. The fluted pumpkin planted in control gave the worst performances. The plots receiving 7.5 t/ha of WSB significantly reduced the soil acidity and increased soil's concentration of Ca, K, and Mg respectively. While, 5 t/ha WSB + 2.5 t/ha PM significantly increased total N concentration, available P and organic matter. The study clearly showed that T. occidentalis leaves yield increased as a result of the addition of WSB and PM, hence WSB had the potential to increase the efficiency of nutrient utilization in the PM. For sustainable fluted pumpkin cultivation in the study area, utilization of 2.5 t/ha WSB + 5 t/ha PM and 7. 5 t/ha PM is therefore recommended.